Foreign Body Extraction Device. Issue 4 (1999) - Lavy, A.
Abstract : Foreign bodies in the gastrointestinal tract are common. Mostly they are swallowed accidentally by children but also by adults. When round and slippery, foreign bodies cause a technical problem for removal. After several days in the stomach they are covered with mucus and extraction becomes even harder. There are various devices designed for use through the flexible endoscope for grasping foreign bodies but due to the great variety of objects, one may face a real problem while trying to remove them. We faced a challenge in a woman who underwent vertical band gastroplasty and was obstructed by a round and slippery hazelnut. We managed to remove the nut using a simple homemade device. This device is easy to make, cheap, and simple to use and maybe useful for various foreign bodies.